Fishing Lake Superior : a complete guide to stream, shoreline, and open-water angling. - Perich, Shawn (University of Minnesota Press, 2002)
At last, an angler's guide to fishing Lake Superior. Whether you're an old salt or an armchair angler, you'll love this book. Experienced fisherman Shawn Perich offers proven tactics for catching steelhead, lake trout, salmon, and walleye, as well as accurate information for boaters, shore-casters, and stream anglers. The straightforward approach of fishing Lake Superior gives clear advice about when, where, and how to hook the big ones.